Evaluation of air pollution modelling tools as environmental engineering courseware - Souto González, J.A.; Bello Bugallo, P.M.; Casares Long, J.J. (Water science and technology, 2004)
The study of phenomena related to the dispersion of pollutants usually takes advantage of the use of mathematical models based on the description of the different processes involved. This educational approach is especially important in air pollution dispersion, when the processes follow a non-linear behaviour so it is difficult to understand the relationships between inputs and outputs, and in a 3D context where it becomes hard to analyze alphanumeric results. In this work, three different software tools, as computer solvers for typical air pollution dispersion phenomena, are presented. Each software tool developed to be implemented on PCs, follows approaches that represent three generations of programming languages (Fortran77, VisualBasic and Java), applied over three different environments: MS-DOS, MS-Windows and the world wide web. The software tools were tested by students of environmental engineering (undergraduate) and chemical engineering (postgraduate), in order to evaluate the ability of these software tools to improve both theoretical and practical knowledge of the air pollution dispersion problem, and the impact of the different environment in the learning process in terms of content, ease of use and visualization of results.